Prospective associations between pre-sleep electronics use and same-night sleep in healthy school-aged children. Issue 3 (3rd July 2021) - So, Christine J.; Gallagher, Matthew W.; Palmer, Cara A.; Alfano, Candice A.
ABSTRACT: Electronic devices are routinely associated with adverse effects on sleep; however, prospective studies among healthy children are unavailable. This study examined relationships among specific and total electronic device use within the hour before bed and same-night sleep patterns among 55 pre-pubertal children (7–11 years) without medical, psychiatric or sleep disorders. Sleep was assessed via subjective reports and actigraphy for 5 weeknights and pre-bed device use was assessed via daily diary. Neither total devices use nor any single type predicted sleep parameters the same night. The extent to which pre-bed electronics use impacts sleep in healthy children requires further investigation.